Challenges and opportunities in patients with adult congenital heart disease, a narrative review - Matteo Fabbri; Anurag Sahu; Anurag Sahu; Anurag Sahu (Frontiers in Cardiovascular Medicine, 2024)
Adult congenital heart disease Pregnancy Transition of care Challenges heart failure.